Interactive 3D human-head multimedia system / Shah Reezal Ahmad - Shah Reezal , Ahmad (2000)
This document was organized in order to give to the reader or user a complete overview about the upcoming project, in the sense that the user should learn the theoretical concepts first and then be aware of how the concepts be applied, being presented meanwhile, some introduction, literation research, methodology, system analysis, system design, system development, system testing, the discussion on the problems occur and examples related with "Interactive 30 human Head Multimedia System". My advisor and supervisor for this thesis is Pn. Nurul Fazmidar Mohd. Noor and the moderator is Dr. Phang Keat Keong. The topic I chose is called "Interactive 30 Human Head Multimedia System". It's a web based projeot and mostly for the purpose of educational, training, medicine and extra general knowledge. I found out that the most important thing in developing a system is that it must be user friendly, easy-to-use, reliable, trustworthy, efficient and fast interaction. Prototyping is important to obtain comments and suggestions from the users to ensure that the final product is high in quality and meet the user's requirements and expectations. This project is concerned with the signal-to-symbol problems of building skinned, segmented, land marked and labeled 30 models of the human bead from range data. A fully automated model·based process is presented that takes raw range data, clean and skin it, and then locates "interesting'' features, to enrich the surface with symbolic information for specific applications. I obtain a lot of useful experience and knowledge through this project undertaking.